2013
DOI: 10.1108/02635571311322757
|View full text |Cite
|
Sign up to set email alerts
|

ICT implementation process model for logistics service providers

Abstract: PurposeInformation and communication technology (ICT) plays a critical role in supporting logistics services outsourcing arrangements. Despite the literature highlighting the benefits of ICT usage by logistics service providers (LSPs), a gap between what is expected of ICT and satisfaction with LSP performance has persisted. Seeking to reduce this gap, the purpose of this paper is to propose an ICT implementation process designed for LSPs.Design/methodology/approachA theoretical model was built, which took int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…India's large and diverse transport and logistics sector faced numerous challenges in the adoption of ITS and Industry 4.0 due to skill and resource constraints. Advanced information technology tools such as GPS technology and tracking and tracing of shipments have been successfully adopted by only 2% of the supply chain companies in India (Luisa et al, 2013). Several international logistics companies in India adopted Industry 4.0 tools like IoT, AI, and machine learning for smart warehousing and logistics.…”
Section: Challenges and Opportunities In Operationalizing The Modelmentioning
confidence: 99%
“…India's large and diverse transport and logistics sector faced numerous challenges in the adoption of ITS and Industry 4.0 due to skill and resource constraints. Advanced information technology tools such as GPS technology and tracking and tracing of shipments have been successfully adopted by only 2% of the supply chain companies in India (Luisa et al, 2013). Several international logistics companies in India adopted Industry 4.0 tools like IoT, AI, and machine learning for smart warehousing and logistics.…”
Section: Challenges and Opportunities In Operationalizing The Modelmentioning
confidence: 99%
“…The utilisation of traditional information and communication technology (ICT) plays a pivotal role in aiding logistical processes (Vieira et al, 2013) and providing visibility across the entire supply chain (Hartono et al, 2010). The extent to which technology is already being operationalised can reflect an organisations readiness to further implement newer forms of technology.…”
Section: Warehousing and Technologymentioning
confidence: 99%
“…Studies in Fintech in the maritime and ports sector have demonstrated the potential benefits and challenges of adoption. Evidence from the literature [13,14,[30][31][32] that matter, the adoption of Fintech in the maritime and ports sector is crucial. Few studies in Africa and beyond have looked at various components of Fintech adoption in the maritime and ports industry.…”
Section: Empirical Reviewmentioning
confidence: 99%